Adjuvanted H5N1 influenza vaccine enhances both cross-reactive memory B cell and strain-specific naive B cell responses in humans - Ellebedy, Ali H.; Nachbagauer, Raffael; Jackson, Katherine J. L.; Dai, Ya-Nan; Han, Julianna; Alsoussi, Wafaa B.; Davis, Carl W.; Stadlbauer, Daniel; Rouphael, Nadine; Chromikova, Veronika; McCausland, Megan; Chang, Cathy Y.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
There is a need for improved influenza vaccines. In this study we compared the antibody responses in humans after vaccination with an AS03-adjuvanted versus nonadjuvanted H5N1 avian influenza virus inactivated vaccine. Healthy young adults received two doses of either formulation 3 wk apart. We found that AS03 significantly enhanced H5 hemagglutinin (HA)-specific plasmablast and antibody responses compared to the nonadjuvanted vaccine. Plasmablast response after the first immunization was exclusively directed to the conserved HA stem region and came from memory B cells. Monoclonal antibodies (mAbs) derived from these plasmablasts had high levels of somatic hypermutation (SHM) and recognized the HA stem region of multiple influenza virus subtypes. Second immunization induced a plasmablast response to the highly variable HA head region. mAbs derived from these plasmablasts exhibited minimal SHM (naive B cell origin) and largely recognized the HA head region of the immunizing H5N1 strain. Interestingly, the antibody response to H5 HA stem region was much lower after the second immunization, and this suppression was most likely due to blocking of these epitopes by stem-specific antibodies induced by the first immunization. Taken together, these findings show that an adjuvanted influenza vaccine can substantially increase antibody responses in humans by effectively recruiting preexisting memory B cells as well as naive B cells into the response. In addition, we show that high levels of preexisting antibody can have a negative effect on boosting. These findings have implications toward the development of a universal influenza vaccine.